Sources, Processing, Transport, Health and Climate Impacts of Air Pollutants - Satoshi Irei; Tak W. Chan (Applied Sciences, 2024)
Atmospheric pollutants exist in both gaseous and particulate form and they have significant impacts on human health, air quality, and the climate [...]